Penerapan Metode Rapid Application Development (RAD) dalam Pengembangan Sistem Informasi Identitas Tanah (SIDENTAH) - Sekar Wulandari; Danendra Saskara; I Nyoman Arya Putra Adnyana (Yayasan Literasi Sains Indonesia, 2026)
Land identity data management at the village level often faces obstacles in terms of access speed, document security, and data accuracy due to the conventional archiving system. This study aims to design and build a web-based Land Identity Information System (SIDENTAH) in Mangunarga Village, Cimanggung District, Sumedang Regency. The system development method used is Rapid Application Development (RAD), which was chosen because of its ability to accelerate the development cycle through the stages of requirements planning, user design, construction, and cutover. The use of RAD allows the active involvement of village officials in the prototyping process so that the resulting system is in accordance with operational needs in the field. The results of the study indicate that SIDENTAH is able to integrate land data into a centralized digital database, simplify the process of searching for land information, and minimize the risk of losing physical documents. Based on User Acceptance Testing by village government employees, the system is stated to function very well worthy of implementation to improve the efficiency of land administration in Mangunarga Village.